Socio-political role of adat perpatih in Negeri Sembilan during British period - Anuar, Nur Asmira; Fathil, Fauziah (IIUM Press, International Islamic University Malaysia, 2017)
Adat Perpatih is one distinctive feature that differentiates Negeri Sembilan from other Malay states in Malaysia which practise Adat Temenggung. Among the prominent values of the customary law derived from a Minangkabau law, Adat Tuah Disakato is matrilineal system, clanship and democracy. Due to lack of study done so far on Adat Perpatih, the book aims to highlight the condition of Adat Perpatih in Negeri Sembilan during the British rule, the nature of relationship between the local Malays and the British colonizers as well as disputes that occurred between both parties and the solutions achieved to end the conflicts. Using the qualitative research technique based on primary and secondary sources, the book shows that even though the influence of Adat Perpatih was overshadowed by the British bureaucratic system, particularly in terms of politics, the customary law continued to have impact especially on the social affairs of the Malays as indicated in the British’s land regulation in Negeri Sembilan. Worth mentioning also is though at first the British and the local Malays had some issues in their relationship, their attitude improved towards one another as time went on through compromise and diplomacy. This partly contributed to the maintenance of Adat Perpatih in the state. The book is expected to encourage the Malays to be proud of their heritage. Finally, many prospective study topics can be conducted in the future.